Assessment of Infertility Factors and Their Relative Impact in Pregnancy using Ultrasonography & Hormonal Checkup - Mohamed Elfadil M. Gar-elnabi; Manal Zainelabdeen Abdelsalam; Mohamed Abdalla Eltahir; Mohammed A. Ali Omer; Mustafa Jafar Musa (Journal of Science and Science Education, 2020)
Infertility as a social and psychological problem among middle east natives. Among them, Transvaginal ultrasound (TVU) and hormonal tests have been selected to evaluate infertility in this study. The objective was to assess the infertility factors and their relative impact in pregnancy and to deduce the equation to predict infertility. Methods: a retrospective data (morphometric pathologies of uterus and ovaries using TVU and laboratory hormones (FSH, LH)) have been collected from clinics for 180 women of reproductive age (15-49 years) in Sudan.  The data analyzed by SPSS. The results showed that there were 120 (66.7%) infertile and 60 (33.3%) fertile ladies based on the marriage date. The common ovarian causes of infertility were the polycystic ovary (PCOs) 23.3%, simple cyst 6.1%, hemorrhagic cyst, 4.4%, and uterus causes: 6.7% intramural fibroma, 6.1% retroverted uterus, 2.8% submural fibroma, 2.2 polyps. The general accuracy of Stepwise Linear Discriminant Analysis (SLDA) was 78.9%, for infertile was 70.8% and for fertile 95%. Larger ovarian width indicates significance (p smaller than 0.05) infertility and FSH level low among infertile ladies, but LH is less dependent on discrimination